The Concept of Holistic Education in the Prophetic Hadith: A Tahlili (Analytical) Study and Its Implementation in the Digital Era - Norlaila, Norlaila; Hudaya, Hairul (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
Holistic education is an educational approach oriented toward the comprehensive development of students through the integration of intellectual, socio-emotional, moral, physical, and spiritual dimensions. This article aims to analyze the concept of holistic education from an Islamic perspective and its relevance in addressing educational challenges in the digital era. The study employed a qualitative approach through a literature review, utilizing the tahlili (analytical) method of hadith analysis and content analysis of relevant literature. The focus of the study is on the hadiths of Prophet Muhammad (peace be upon him) that emphasize the integration of faith, knowledge, moral character, and social responsibility, such as the hadith on the perfection of faith measured by moral conduct, the obligation to seek knowledge, the value of social benefit, and the prophetic mission to perfect noble character. The findings indicate that Islamic education normatively emphasizes the formation of the insan kamil (the complete human being), characterized by a balance of intellectual, spiritual, emotional, and social intelligence. This concept aligns with the principles of holistic education, which position students as active subjects in a comprehensive developmental process. In the context of the digital era marked by technological advancement, robotization, and automation holistic education represents a strategic approach, as it not only equips students with 21st-century knowledge and skills but also strengthens moral values, character formation, and social responsibility. Although its implementation faces challenges, including resistance to paradigm shifts in education and unequal access to technology, the use of digital technology, distance learning, and collaboration between education and industry offers significant opportunities to reinforce sustainable and inclusive holistic education.